HOUSEHOLD VIOLENCE CAUSED BY NARCOTICS ABUSE (RESEARCH AT AL KAMAL SIBOLANGIT CENTER FOR DRUG REHABILITATION) - Gomgom TP Siregar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2023)
Violence perpetrated by husbands against wives often occurs, in fact one out of three wives has experienced domestic violence. The problem in this research is how to regulate the law against perpetrators of domestic violence (KDRT) caused by narcotics abuse, how are the efforts of the Al Kamal rehabilitation center in dealing with criminal acts of domestic violence (KDRT) caused by narcotics abuse. The conclusion in this study, it is known that domestic violence is a combination effect and interaction of biological, psychological, economic, and political factors such as a history of violence. Overcoming criminal acts of domestic violence caused by drug abuse is through rehabilitation. It is suggested that the rehabilitation rights of narcotics addicts and victims are protected in carrying out the benefits of rehabilitation efforts in recovery. It is necessary to improve the monitoring system for rehabilitation beneficiaries and to have implementation guidelines that become service standards at the Al Kamal Rehabilitation Center. The form of supervision referred to is consistent monitoring from the social ministry of the Al Kamal Rehabilitation Center.